High Volume Center Experience for Recurrent Primary Disease in Kidney Transplanted Pediatric - Afshin, Azadeh; Sharifian, Mostafa; Simfroosh, Naser; Basiri, Abbas; Lotfollahzadeh, Saran; Esfandiar, Nasrin (Journal of Pediatric Nephrology, 2019)
Introduction: Over the past 3 decades, kidney transplantation has been recognized as the treatment of choice for children with End Stage Renal Disease (ESRD) and stage 5 of chronic kidney disease (CKD). One of the most important drawbacks to this treatment is the recurrence of the primary disease in the transplanted kidney, which is considered the third most common leading cause of graft failure. Materials & Methods: In this study, the data of 550 patients below 18 years who underwent kidney transplantation during a 33-year period from 1985 to 2017 due to kidney failure or ESRD were included to fill out a standard questionnaire. Those who suffered from primary disease relapse were included in the study to investigate the association of relapse with factors such as gender, age, and donor type, time to relapse with type of disease, and post-transplant immunosuppressive drugs with severity of pre-transplant kidney injury. Results: Of 31 pediatric patients with primary disease recurrence (out of 550 transplanted kidney), 62.5% were male with a mean age of 10.55 (± 0.665) years. Totally, 10 cases showed recurrence of the primary disease 18 (± 22.95) months after transplantation on average. The final status of these 10 patients was significantly undesirable compared with that of the other 21 patients without recurrence (p= 0.002). Of these 10 patients, 8 had graft failure. Conclusion: The results of this report confirm the necessity of follow-up considering the importance of the recurrence of the primary disease, especially FSGS, in children after kidney transplantation.